Analysis of Students Cognitive and Social Reading Strategies in Reading Comprehension at The Third Semester - Dwi Megista Putri (Universitas Putra Indonesia YPTK Padang, 2019)
This study examined students’ cognitive and social reading strategies in Economic and Business Department of UPI YPTK Padang. A total of 156 students in three classes were surveyed regarding their reading strategies. The method used in this research was descriptive correlation method. 15 students were taken as samples by using random sampling technique. The results found that there were high statistically significant correlation among the three classes. These findings were discussed in regards to whether correlation in reading strategies could potentially influence learning outcomes and effectiveness of teaching reading